Pendekatan Sosiolinguistik dalam Pembelajaran BIPA Berbasis Budaya Lokal untuk Meningkatkan Kompetensi Komunikatif Pemelajar - Sari Sulfiana; Abdul Azis (Universitas Pahlawan Tuanku Tambusai, 2026)
Globalization has increased international interest in learning Indonesian through BIPA (Indonesian for Foreign Speakers), which emphasizes not only linguistic aspects but also social and cultural contexts. This article aims to examine the concept of sociolinguistics, its application in BIPA learning based on local culture, and its impacts and challenges. The method used is a literature review. The findings show that a sociolinguistic approach enhances learners’ communicative competence through understanding social context, language variation, and politeness norms. The integration of local culture provides authentic contexts that strengthen pragmatic and intercultural competence. However, its implementation still faces challenges such as limited teaching materials and teachers’ competencies. Therefore, the development of local culture-based teaching materials and the improvement of teachers’ competencies are needed to make learning more effective and contextual.